Differential Recruitment of Nuclear Coregulators Directs the Isoform-Dependent Action of Mutant Thyroid Hormone Receptors - Fozzatti, Laura (Endocrine Society, 2011)
Studies using mice deficient in thyroid hormone receptors (TR) indicate that the two TR isoforms, TRα1 and TRβ1, in addition to mediating overlapping biological activities of the thyroid hormone, T3, also mediate distinct functions. Mice harboring an identical dominant negative mutation (denoted PV) at the C terminus of TRα1 (Thra1(PV) mice) or β1 (Thrb(PV) mice) also exhibit distinct phenotypes. These knockin mutant mice provide an opportunity to understand the molecular basis of isoform-dependent functions in vivo. Here we tested the hypothesis that the distinct functions of TR mutant isoforms are directed by a subset of nuclear regulatory proteins. Tandem-affinity chromatography of HeLa nuclear extracts showed that distinct 33 nuclear proteins including nuclear receptor corepressor (NCoR1) and six other proteins preferentially associated with TRα1PV or TRβ1PV, respectively. These results indicate that recruitment of nuclear regulatory proteins by TR mutants is subtype dependent. The involvement of NCoR1 in mediating the distinct liver phenotype of Thra1(PV) and Thrb(PV) mice was further explored. NCoR1 preferentially interacted with TRα1PV rather than with TRβ1PV. NCoR1 was recruited more avidly to the thyroid hormone response element-bound TRα1PV than to TRβ1PV in the promoter of the CCAAT/enhancer-binding protein α gene to repress its expression in the liver of Thra1(PV) mice, but not in Thrb(PV) mice. This preferential recruitment of NCoR1 by mutant isoforms could contribute, at least in part, to the distinct liver lipid phenotype of these mutant mice. The present study highlights a novel mechanism by which TR isoforms direct their selective functions via preferential recruitment of a subset of nuclear coregulatory proteins.